The Effect of Application Guessing Game Pic-Pow Strategy Towards Students’ Speaking Mastery at the First Class of SMA Mathla’ul Anwar Menes - Karlina, Karlina; Sudirman, Ade (Journal of English Education Studies, 2019)
This research aims to investigate the effect of application guessing game pic-pow strategy towards students’ speaking mastery at the first class of SMA Mathla’ul Anwar Menes. It employs the quantitative research with the characteristics of the true experimental design. It uses achievement test in collecting data involving orally pre and post tests. The findings reveal that application guessing game pic-pow strategy is able to help students to improve their speaking skill mastery. In the pre-test, the mean of experimental class is 38 and the mean of control class is 39, 13 while in the post-test the mean of experimental class is 92,75 and mean of control class is 79, 29. In the post test of t-test, the researcher can conclude that tcount ≥ ttable or 3, 0858 ≥ 1, 672 therefore Ha is accepted and there is a significant effect of application guessing game pic-pow strategy towards students’ speaking mastery.